Green threads of change: Unravelling the gendered and experienced moderators in the sustainable symphony of green HR practices and environmental responsibility - Altassan, Megren Abdullah; Ahmad, Aqeel (International Journal of Innovative Research and Scientific Studies, 2024)
This study employs a quantitative methodology to investigate the intricate relationships between Green Human Resource (HR) Practices, Green Culture, and Environmental Sustainability. The independent variable, Green HR Practices, is delineated into four components: green recruitment, green training, green reward, and green empowerment. The mediating role of Green Culture is explored in the context of two dependent variables: Proactive Organization-Centered Environmental Sustainability and Reactive Organization Eco-Centric Environmental Sustainability. Additionally, gender and experience are introduced as moderators, influencing the relationship between Green Culture and the two dimensions of Environmental Sustainability. Utilizing a purposive sampling technique, data were collected from 357 participants from industries in Pakistan. The analysis was conducted using Warp-PLS 8.0 software. The results reveal significant direct and indirect effects of Green HR Practices on both and, with Green Culture acting as a mediator. The study further unveils the moderating influence of gender and experience on the relationship between Green Culture and Environmental Sustainability. Key findings include the identification of specific Green HR Practices that significantly impact environmental outcomes. The mediating role of Green Culture elucidates the pathway through which these practices influence sustainability. The moderation effects of gender and experience underscore the nuanced nature of these relationships, emphasizing the need for tailored strategies. The study contributes to the growing literature on sustainable HR practices by offering insights into the mechanisms driving environmental sustainability within organizations. The findings have practical implications for HR practitioners, highlighting the importance of cultivating green organizational culture and considering individual differences in the implementation of sustainability initiatives.